(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
The work of Danie Strauss has always been a celebration of systematic analysis in the reformational tradition. In this contribution, I consider how such an analysis may shed light on the nature of a specific discipline, applied linguistics. Not only is reformational philosophy able to delimit this field in a useful way, but it is also capable of illuminating historical turning points in the discipline. Both historically and philosophically, the modernist approach characteristic of first generation applied linguistics lies at one end of the discipline, and current, postmodernist perspectives at the other extreme. While modernist definitions of the field have emphasised the theoretical, scientific basis of the discipline, and postmodernist definitions identify (social and political) accountability as the critical feature of the endeavour, the discipline of applied linguistics finds a common feature in the moment of design. The argument presented is that the contributions of modernist and postmodernist approaches to applied linguistics can both be honoured in a systematic analysis. The paper concludes that a systematic explanation directs us towards a responsible agenda for applied linguistics.